The Philosophy of Sarong Motifs as a Teaching Material Development Based on Local Wisdom of Kui Ethnicity, Southwest Alor District, Alor Regency - Bustami M Kaibana; Rudy Gunawan; Lelly Qodariah (Borong Newinera Publisher, 2024)
This research aims to describe the ethnic system of the Kui ethnic community, the motifs on Kui ethnic sarongs as social studies teaching materials based on local wisdom, develop social studies teaching materials that are integrated with local wisdom values in increasing the creativity of students in the Southwest Alor community, Alor Regency and determine the feasibility Kui Ethnic sarong philosophy as the development of social studies teaching materials based on local wisdom in increasing the creativity of students in the Southwest Alor community, Alor Regency. The research method used in this research is research and development (R&D). This research uses the Borg & Gall model. The data collection techniques used were questionnaires and documentation using assessment sheets based on material experts, media experts and teacher responses as research instruments. The results of the research show that the social studies teaching materials based on local wisdom that were developed are suitable for use in social studies learning. This is proven by the results of the assessment of material experts, media experts, and teacher responses which are in the very appropriate category. The conclusion of the research shows that social studies teaching materials based on local wisdom that integrate the local wisdom values of the Kui ethnic group in the Southwest Alor community of Alor Regency have been developed, these teaching materials are suitable for use in social studies learning.